Evaluation of in vivo T cell kinetics: use of heavy isotope labelling in type 1 diabetes. (18th April 2013) - Bollyky, J. B.; Long, S. A.; Fitch, M.; Bollyky, P. L.; Rieck, M.; Rogers, R.; Samuels, P. L.; Sanda, S.; Buckner, J. H.; Hellerstein, M. K.; Greenbaum, C. J.
Summary CD4+ memory cell development is dependent upon T cell receptor (TCR) signal strength, antigen dose and the cytokine milieu, all of which are altered in type 1 diabetes (T1D). We hypothesized that CD4+ T cell turnover would be greater in type 1 diabetes subjects compared to controls. In vitro studies of T cell function are unable to evaluate dynamic aspects of immune cell homoeostasis. Therefore, we used deuterium oxide (2H2O) to assess in vivo turnover of CD4+ T cell subsets in T1D (n = 10) and control subjects (n = 10). Serial samples of naive, memory and regulatory (Treg) CD4+ T cell subsets were collected and enrichment of deoxyribose was determined by gas chromatography–mass spectrometry (GC–MS). Quantification of T cell turnover was performed using mathematical models to estimate fractional enrichment (f, n = 20), turnover rate (k, n = 20), proliferation (p, n = 10) and disappearance (d*, n = 10). Although turnover of Tregs was greater than memory and naive cells in both controls and T1D subjects, no differences were seen between T1D and controls in Treg or naive kinetics. However, turnover of CD4+ memory T cells was faster in those with T1D compared to control subjects. Measurement and modelling of incorporated deuterium is useful for evaluating the in vivo kinetics of immune cells in T1D and could be incorporated into studies of the natural history of disease or clinical trials designed to alter the disease course. The enhanced CD4+ memory T cell turnover in T1D may be important in understanding the pathophysiology and potential treatments of autoimmune diabetes.